Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/molecules24183267
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Iron(III) Selective Fluorescent Probes with Possible Applications in Bioimaging

Abstract: Iron(III) is well-known to play a vital role in a variety of metabolic processes in almost all living systems, including the human body. However, the excess or deficiency of Fe3+ from the normal permissible limit can cause serious health problems. Therefore, novel analytical methods are developed for the simple, direct, and cost-effective monitoring of Fe3+ concentration in various environmental and biological samples. Because of the high selectivity and sensitivity, fast response time, and simplicity, the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 85 publications
1
31
0
1
Order By: Relevance
“…Similar studies with alternative synthetic analogues bearing coumarine moiety with an ester functional inside the ring pointed out the importance of the lactone group for the specific interaction with Iron (III) [17]. Although majority of the study in the relevant field focuses more on the development of OFF-ON type probes for selective Iron (III) detection, this type of approach through On-OFF strategy generates alternative probes [18][19].…”
Section: Resultsmentioning
confidence: 96%
“…Similar studies with alternative synthetic analogues bearing coumarine moiety with an ester functional inside the ring pointed out the importance of the lactone group for the specific interaction with Iron (III) [17]. Although majority of the study in the relevant field focuses more on the development of OFF-ON type probes for selective Iron (III) detection, this type of approach through On-OFF strategy generates alternative probes [18][19].…”
Section: Resultsmentioning
confidence: 96%
“…This dye crosses cell membranes and is captured by mitochondria without inducing cell lysis. Rhodamine-based dyes can be used to bioimage iron pools in living cells [37]. Almost all cells from the control sample not subjected to PEF and without iron supplementation were dark (Figure 7A), whereas those from the sample enriched with iron without PEF partly showed green fluorescence (Figure 7B).…”
Section: Fluorescence Imaging Of Yeast Cellsmentioning
confidence: 99%
“…The selectivity and the tolerance of UiO-66-N-Py for Fe 3+ as compared to other metal pollutants was examined by immersion of the MOF into aqueous solution of various metal ions (e.g., Fe 2+ , Fe 3+ , Co 2+ , Cu 2+ , Ni 2+ , Zn 2+ , Cd 2+ , Hg 2+ , Ag + , Pd 2+ , Al 3+ , Ga 3+ , Pb 2+ Na + , K + , Ca 2+ , Mg 2+ , Sr 2+ , Rb 2+ , and Cs 2+ ) ( Figure 6, and Figure S14 in Supplementary Materials). It was observed that complete emission suppression occurs only in the case of Fe 3+ due to its paramagnetic nature, and proximity of the pyridine nitrogen with the imine group helps in selective binding of the Fe 3+ as compared to the other cations [25]. PXRD of UiO-66-N-Py bounded with Fe 3+ indicated that the framework's crystallinity is not disturbed (Figure 2).…”
Section: Cation Sensing Properties Of Uio-66-n-pymentioning
confidence: 99%